The Research on CAI Hongsheng’s Academic Achivemengts and Characteristics of the History of Western Regions - Wang Gui Lian (International Journal on Integrated Education, 2022)
This article describes the famous Chinese historian Cai Hongsheng’s life experience in detail, analyzes Mr.Cai’s academic characteristics and achievements in the field of the Western Regions, and objectively evaluates his contributions in promoting academic development and cultivating talents.